STUDY ON AE SIGNALS OF OXYGEN FREE COPPER SCRATCHING WITH SINGLE DIAMOND ABRASIVE GRIT - WU HaiYong; HUANG Hui (Jixie qiangdu)
Acoustic emission（ AE） signals with different scratch speeds,feed rates and scratch depths were measured and analyzed for the oxygen free copper scratching with single diamond abrasive to research the cutting mechanism of oxygen free copper. The influences of the characteristic parameters,time-domain signals,frequency spectrum and power spectrum of the AE on the different scratching parameters were analyzed and discussed. The results show that the scratch depth has the significant influence on the AE signals. The effects of scratch speeds and feed rate on AE signals are not distinct. The main frequency of single diamond grit scratching on oxygen free copper is dominant on the frequency band of 0-170 kH z. The main frequency value of the power spectrum decreases with the increasing of scratch depths.